Estimation of soil erosion and risk assessment in Somalia (International Journal of Agricultural Research, Innovation and Technology, 2025)
Soil erosion is a pressing issue that threatens environmental stability and agricultural productivity across the globe. In Somalia, where the population already contends with severe socioeconomic and environmental challenges, the effects of erosion compound problems like food insecurity and land degradation. This study investigates erosion patterns and identifies areas prone to soil loss, aiming to provide actionable insights for improving land use practices and resource management. The research employs advanced analytical tools to study how erosion factors are distributed geographically. Data such as terrain characteristics, rainfall intensity, vegetation cover, soil quality, and land usage are systematically analyzed. Cutting-edge modeling techniques, supported by historical erosion trends, help to develop accurate predictions about future soil loss, offering a robust basis for creating effective intervention strategies. The findings show that many regions in Somalia are highly susceptible to erosion, particularly where unsustainable human activities such as overgrazing, deforestation, and improper farming methods are prevalent. These insights underscore the urgent need for targeted policies to mitigate erosion and protect valuable soil resources. By forecasting potential erosion scenarios, this research equips decision-makers with the tools needed to prioritize interventions that enhance agricultural output, preserve ecosystems, and ensure long-term sustainability. This research aids policymakers, land managers, and stakeholders in formulating focused, evidence-based plans for soil conservation and sustainable land use, ultimately facilitating the preservation and enhancement of Somalia's natural resources and agricultural resilience.Int. J. Agril. Res. Innov. Tech. 14(2): 111-121, December 2024